204k views
4 votes
9. Simplify 1/2 (4a + b) - 1/4 (4a + b)

А. a
B. a + 1/4 b
C. 2a + 1/4 b
D. 2a - b

User Rosary
by
4.6k points

2 Answers

3 votes

B.
a + (1)/(4) b

Step-by-step Step-by-step explanation:


(1)/(2) (4a + b) - (1)/(4) (4a + b) \\ = (4a + b)/(2) - (4a + b)/(4) \\ = (2(4a + b))/(2 * 2) - (4a + b)/(4) \\ = (8a + 2b)/(4) - (4a + b)/(4) \\ = (8a + 2b - 4a - b)/(4) \\ = (4a + b)/(4) \\ = (4a)/(4) + (b)/(4) \\ = a \: + (1)/(4) b


\circ \: \: { \underline{ \boxed{ \sf{ \color{green}{Happy\:learning.}}}}}∘

User Youngtackpark
by
4.9k points
3 votes

B: a+ 1/4b Hope this helps!

User Tomas Smagurauskas
by
5.3k points